BUNGA BANK DALAM PERSPEKTIF ISLAM (STUDI PENDAPAT NAHDLATUL ULAMA DAN MUHAMMADIYAH) - Abdul Salam (JESI (Jurnal Ekonomi Syariah Indonesia), 2013)
Abstract One of the problems is crowded and is still being debated in the Islamic economy is a matter of usury which is forbidden in the Koran . This debate mainly focused on what is really meant by riba in the Qur'an and how the economy of the Muslims who are held in the middle of the current capitalist economy and modern banking practices that require interest in economic activity .In existential presence of banking institutions can not be separated from economic problems of Muslims as a whole . Muslims who live in the modern system of value-free economy can not escape the " dependency " with banking institutions . consciously or unconsciously banking institutions have been brought up to the Muslims to accept the reality of banking today . It is then disturb the attention of many Muslim community organizations in Indonesia to revisit karaktreristik prohibited usury , presumably withdraw in this case the researchers raised two Islamic society organizations that have a large period of the Nahdhotul Ulama ( NU ) and Muhammadiyah . Where the existence of this organization opposing the giving fatwa against religious issues in society . The subject of this paper is to examine how the public views the two organizations on bank interest .From in-depth discussion can be concluded that : For NU that bank interest law it is forbidden either privately owned banks and state-owned banks . Furthermore , NU revealed that the interest taken by depositors in the bank is forbidden usury . As for Muhammadiyah presumably still skeptical about the presence or absence of ' usury illat on state-owned banks , as seen with the determination , that the law is a state -owned bank interest musytabihat . Reason said musytabihat , is because there are two tendencies are lawful or unlawful , as well as in a bank that does not distinguish between people who borrow money to borrow for consumption and produced . Then this should be avoided , except in an emergency ( forced ) . Muhammadiyah 's decision seems consistent with the notion that interest rates may have an emergency , such as Mustafa az - Zarqani opinion , saying that the bank is a reality that can not be avoided . Therefore Muslims should bermu'amalah with the bank for emergency consideration. Furthermore , Muhammadiyah states , that usury is forbidden by religion is flowering trait that is always accompanied by substance abuse and oppression chance . Being in force today did not cause a sense of oppression or disappointment by anyone interested Keywords: Bank, Interest, Riba, Nahdhotul Ulama, Muhammadiyah